The Social Management of Human Resources in Organisations - GUEMMADI , Takwa (Milev Journal of Research and Studies, 2020)
This study aims to show the social role of human resources function in the institution which believes that the person is a strategic partner and a source of its distinction and its ability to realize unprecedented achievements. As a member of the community it is required to commit social and ethical responsibilities towards human resources in all the stages going through, either when applying for a job in the institution as shown attract and selection processes, or in recruitment when its shown by extent of security and safety at work, health care, fair salary, leadership and supervision type, recognition and appreciation, giving opportunities for learning, encouraging progress and creativity, or at the end of career life cycle and separation from work.